DETERMINANTS AND CONSEQUENCES OF CORPORATE COMMUNICATION MANAGEMENT: REVIEW OF THE CURRENT LITERATURE AND A CONCEPTUAL MODEL - Bahtiar Mohamad; Hassan Abu Bakar (Jurnal Manajemen Pemasaran, 2008)
This paper is a literature review which analyses the influences of managerial communication, marketing communication and organizational communication on corporate communication. In addition, this paper shows how corporate communication management influences organizational performance. The paper also investigates the role of corporate leadership in moderating the relationship between corporate communication and organizational performance. An integrative framework and a detailed summary table are provided. Three categories of determinants, namely, management communication, marketing communication and organizational communication are gathered from the literature. Direct consequences and indirect consequences through relevant mediators are identified. Future research directions are also offered. The compendium of determinants and consequences of Corporate Communication Management can be used by corporate communication practitioners to segment and target stakeholders